A community approach to promote healthcare services for people living with HIV who use drugs in Vietnam. (February 2022) - Li, Li; Lin, Chunqing; Liang, Li-Jung; Song, Weilu; Pham, Loc Quang; Le, Tuan Anh; Nguyen, Tuan Anh
Background: People living with HIV who use drugs (PLHWUD) face enormous challenges to access antiretroviral therapy (ART), addiction treatment, and other healthcare services. This study evaluated the effect of a community capacity-building approach on PLHWUD's access to healthcare services. Methods: A cluster randomized controlled trial was conducted in four provinces of Vietnam. Trained commune health workers in the intervention condition were encouraged to provide services to PLHWUD in the community and engage them in HIV/addiction treatment and care using learned knowledge and skills. A total of 241 PLHWUD participated in surveys at the baseline and every three months for one year. The primary outcome was PLHWUD's reported barriers to seeking healthcare. A linear mixed-effects regression model with a difference in difference approach was used to estimate the intervention effect on the primary outcome. Results: Adjusted analyses indicated that significant intervention effects were observed at the Sixth and ninth month follow-ups for those on ART at the baseline and increased motivation to engage in treatment at the 3-month follow-up (60.2% vs 34.4% for the intervention and control groups, respectively). Conclusions: The community capacity-building intervention had shown promising yet limited outcomes among a subset of PLHWUD in the community, that is, PLHWUD who had already initiated ART.